A statistical models to predict strength development of eight molarity geopolymer concrete - Ali A. Ali; Tareq S. Al-Attar; Waleed A. Abbas (Case Studies in Construction Materials, 2022)
Geopolymer concrete has emerged as a viable alternative to traditional concrete. Geopolymer is amorphous to semi-crystalline materials synthesized from materials generally containing SiO2 and Al2O3 compounds as a source of aluminosilicates. This study aims to develop and validate statistical models to predict the strength development of Geopolymer concrete with 8 molarity of NaOH using data from current experimental work as well as experimental data gathered from local and international literature with different R ratios; SiO2/Al2O3. The present experimental study used binary and ternary systems of source materials, Fly ash FA, Ground Granulated Blast-furnace Slag GGBS, and Metakaolin MK, to achieve different percentages of R ratios ranging from 1.42 to 3.6. Seven Geopolymer concrete mixes with varied R ratios were used in the current experimental portion of the inquiry. Compressive, splitting, and flexural strengths were the characteristics determined. Based on the findings of the trials, it was found that the R ratio has a considerable impact on the mechanical performance of the final product. Results showed that; the compressive strength, splitting tensile strength, and flexural strength at the highest value of R ratio of 3.6 used increased by 362%, 272%, and 333%, respectively, compared with those strengths at the lower R ratio of 2.01 used. Linear and non-linear regression analyses were performed by the Statistical Package for the Social Sciences (SPSS) software version 25 to generate the developed models. The statistical models indicated that the R ratio could reasonably estimate the geopolymer's strength with a statistical correlation coefficient of 0.86, 0.93, and 0.86 for compressive, splitting, and flexural strengths.